HUBUNGAN ANTARA MOTIVASI AKADEMIK DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA - Reza, Iredho Fani (HUMANITAS, 2015)
AbstractThis research was intended to find out the correlation between academik motivation and academic procastination on post garduate students. The population of the study was taken from magister students of a postgraduate school in Jakarta during the period of 2010-2014. The sampling technique used purposive sampling and involved 30 post graduate students as samples. Data were collected through Academic Motivation Scale and Academic Procastinantion Scale and were analized using product moment correlation technique. Result showed that the correlation coefficient between values r = 0.348 with a significance p=0.059 (p ≥ 0.05), it means that there was insignificant relationship between motivations and academic procrastination on post graduate students. Based on the data analysis, the study concludes that there is no significant correlation to academic procrastination on magister students. It suggests that magister students’ motivation is not significant to reducingbehavior of academic procrastination.Keywords: academic motivation, academic procrastination, motivation